Rheumatoid Arthritis: A review of current treatment option - Premkumar, P.; M.Nair, Nikhila.; Abraham, Jency; Abraham, Shajan (Journal of Neonatal Surgery, 2025)
Rheumatoid Arthritis (RA) is a chronic autoimmune disease that affects mostly the joints. It causes swelling, pain, stiffness in joints. Recently, disease modifying drugs and the new classes of medications has improved the outcomes that can satisfy most patients. The main aim of the therapy or treatment is achieving the lowest possible levels of arthritis disease activity and remission thereby reducing joint damage, and enhancing physical function and quality of life. The present scenario of treatment requires a comprehensive program which combines medical, social, and emotional support for the patient. There are several classes of drugs used in treatment of RA with some side-effects from which Disease Modifying Anti- Rheumatic Drugs (DMARD’s) have shown to alter the disease cause and have an improved radiographic outcomes. Emerging trends in RA treatment, includes mesenchymal stem cell therapies and biosimilar drugs. This comprehensive review aims to provide healthcare professionals and patients with a solid understanding of the current treatment options for RA, making possible of the informed decision-making and good management of the disease.